IDENTIFIKASI STRATEGI PEMASARAN TEMPE SUCIPTO DI KOTA MANADO - Nurfadila ., nfn; Juliana R. Mandei; Lorraine W. Th. Sondak (AGRI-SOSIOEKONOMI, 2018)
The purpose of this study is to find out the marketing strategy of Tempe Sucipto in Manado. This study uses descriptive analysis based on Likert scale. This study is conducted from November until January 2018 located in MultiMart, Jumbo, Golden, Fiesta Ria, Transmart Carrefour, and Indomaret Plus Manado. The data used are primary data and secondary data. Primary data is obtained from interview towards 12 respondents of customers of Tempe Sucipto who have ordered Tempe Sucipto in November 2018. Secondary data is data obtained from the related literature. Results indicate that respondents are satisfied to the product Tempe Sucipto in terms of quality. Packaging, durability, and features.*lrr*.